Association of leisure-time physical activity with perceived general health status among hypertensive people: An analysis of NHANES 2015–18 - Al Kibria, Gulam Muhammed; Gupta, Rajat Das; Crispen, Reese (Nature, 2022)
This article was published in the Journal of Human Hypertension by Nature [Copyright © 2021, The Author(s), under exclusive licence to Springer Nature Limited] and the definite version is available at: https://doi.org/10.1038/s41371-021-00518-3 The Journal's website is at: https://www.nature.com/articles/s41371-021-00518-3